Molecular analysis of enthesopathy in a mouse model of hypophosphatemic rickets - Liu, Eva S.; Martins, Janaina S.; Zhang, Wanlin; Demay, Marie B. (Development (Cambridge), 2018)
The bone tendon attachment site known as the enthesis comprises a transitional zone between bone and tendon, and plays an important role in enabling movement at this site. X-linked hypophosphatemia (XLH) is characterized by impaired activation of vitamin D, elevated serum FGF23 levels and low serum phosphate levels, which impair bone mineralization. Paradoxically, an important complication of XLH is mineralization of the enthesis (enthesopathy). Studies were undertaken to identify the cellular and molecular pathways important for normal post-natal enthesis maturation and to examine their role during the development of enthesopathy in mice with XLH (Hyp). The Achilles tendon entheses of Hyp mice demonstrate an expansion of hypertrophic-appearing chondrogenic cells by P14. Post-natally, cells in wild-type and Hyp entheses similarly descend from scleraxis- and Sox9-expressing progenitors; however, Hyp entheses exhibit an expansion of Sox9-expressing cells, and enhanced BMP and IHH signaling. These results support a role for enhanced BMP and IHH signaling in the development of enthesopathy in XLH.